2021
DOI: 10.14740/jocmr4401
|View full text |Cite
|
Sign up to set email alerts
|

Body Muscle-to-Fat Ratio, Rather Than Fat-to-Muscle Ratio, Significantly Correlates With Measured Insulin Resistance in Patients With Type 2 Diabetes Mellitus

Abstract: Background: Insulin resistance (IR) assessment is important in treating type 2 diabetes mellitus (T2DM). We thus compared body muscle-to-fat ratio (BMFR) and fat-to-muscle ratio (FMR) values against M/I values as clinical index of IR.Methods: Subject included 118 untreated T2DM patients. Hyperinsulinemic-euglycemic clamp examination was performed to calculate the M/I as index of IR. Body composition was measured by impedance analysis using InBody770.Results: Simple linear regression analyses confirmed correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…However, we regard the muscle-to-fat ratio as a more significant indicator because it provided the approach to reducing metabolic disorder risks by elevating the muscle mass and simultaneously reducing the fat mass. A previous study also suggested that the muscle-to-fat ratio was a better indicator than the fat-to-muscle ratio in quantifying insulin resistance ( 37 ).…”
Section: Discussionmentioning
confidence: 98%
“…However, we regard the muscle-to-fat ratio as a more significant indicator because it provided the approach to reducing metabolic disorder risks by elevating the muscle mass and simultaneously reducing the fat mass. A previous study also suggested that the muscle-to-fat ratio was a better indicator than the fat-to-muscle ratio in quantifying insulin resistance ( 37 ).…”
Section: Discussionmentioning
confidence: 98%
“…Lean mass is primarily composed of skeletal muscle, an active metabolic tissue known for its role in insulin sensitivity and glucose uptake [ 41 ] and has been positively related to metabolic health [ 41 - 43 ]. Consistent with this idea, other studies analyzing the muscle-to-fat mass ratio demonstrated its high diagnostic accuracy for MetS [ 44 ] and insulin sensitivity measured by hyperinsulinemic-euglycemic clamp [ 45 , 46 ]. Individuals presenting low values of this index were more likely to exhibit a higher prevalence of MetS and its components [ 44 ].…”
Section: Discussionmentioning
confidence: 57%